Systemic metastases in large cell neuroendocrine prostate cancer: a rare case report and literature review - Xiao, Maolin; Tong, Wei; Xiao, Xiao; Pu, Xiaofeng; Yi, Faxian (Frontiers in Oncology, 2024)
Neuroendocrine prostate neoplasms, encompassing small cell carcinoma, carcinoid, and large cell carcinoma, are infrequently observed in malignant prostate tumors. The occurrence of large cell neuroendocrine prostate cancer (LCNEPC) is exceedingly rare. In this study, the patient initially presented with a persistent dysuria for a duration of one year, accompanied by a serum prostate-specific antigen (PSA) level of 17.83ng/mL. Prostate magnetic resonance imaging (MRI) and chest computed tomography (CT) scan showed that a neoplastic lesion was considered, and prostate biopsy confirmed prostate adenocarcinoma with a Gleason score of 7 (4 + 3). Then, thoracoscopic lung tumor resection was performed, and the pathological examination revealed the presence of primary moderately differentiated invasive adenocarcinoma of the lung and metastatic prostate adenocarcinoma, the Gleason score was 8 (4 + 4). After 1 year of endocrine therapy with goserelin acetate and bicalutamide, he underwent a laparoscopic radical prostatectomy (LRP), the pathological report indicated the presence of adenocarcinoma mixed with NE carcinoma. Two months after the LRP, the patient experienced gross hematuria and sacral tail pain. Further examination revealed multiple metastatic lesions throughout the body. He also underwent transurethral resection of bladder tumor (TURBT) for bladder tumor and received etoposide+ cisplatin chemotherapy three weeks post-surgery. The patient eventually died of multi-organ failure due to myelosuppression after chemotherapy. This case report presents an uncommon instance of LCNEPC with widespread systemic metastases, while also providing a comprehensive review of existing literature to facilitate improved management and treatment strategies for similar patients in subsequent cases.